Application Of PBL Model in Improving Students' Independence in Islamic Religious Education Subjects In Class XI Of State Vocational High School 8 Medan - Putri Zahra; Bahtiar Siregar (Yayasan Multidimensi Kreatif, 2025)
Independence Study as one of the aspect crucial students in the learning process who play a role in development potential self . Study of study This related application of the PBL model in improvement independence students at SMK Negeri 8. Research This started from lack of optimization in independence Study tend cause student not enough believe self so that No maximize the abilities that exist within him . Applying method qualitative descriptive , utilizing the process of observation , interviews , and studies documentation as technique collection data.Technique data analysis using stages data reduction , data presentation , then withdrawal conclusion . Findings than study disclose that There is improvement independence student with the implementation of the PBL model , namely skills breakdown problem,ability think critical , and strengthening mark trust self . The implementation of the PBL model must be in accordance with the steps and consistency is an important thing in increasing student independence. The conclusion is that with PBL implementation , independence Study student can increased in eyes Islamic Religious Education lesson in class XI Culinary Arts 7.